RESTRUKTURISASI FINALITAS PUTUSAN DALAM PERADILAN ADMINISTRASI: Analisis Putusan Mahkamah Konstitusi Nomor 24/PUU-XXII/2024 - Muh. Ferdiansyah; Ahmad Rustan; Fachmi Jambak (Jurnal Hukum to-ra : Hukum untuk mengatur dan melindungi masyarakat, 2026)
Constitutional Court Decision Number 24/PUU-XXII/2024 limits the right of State Administrative Officials to file a judicial review (PK) in administrative disputes. This decision arose from a classic problem in administrative justice, namely officials' non-compliance with final decisions and the use of PK as an instrument to delay execution. This article aims to analyze the construction of the Court's legal reasoning and its normative implications for legal certainty, justice, and the effectiveness of the implementation of PTUN decisions. As a normative legal research, this study uses a statutory law approach, a case approach, and a conceptual approach. The analysis is conducted through a systematic and teleological interpretation of norms and the use of the theories of finality (res judicata), proportionality, and the rule of law (rechtsstaat). The results show that the limitation of PK is not merely a procedural limitation, but rather a restructuring of the model of judicial control over administrative power. This decision strengthens the finality of decisions and the protection of citizens' constitutional rights, but has the potential to create institutional tensions if not followed by regulatory harmonization. This article emphasizes that the decision marks a paradigm shift from a formal procedural model to a constitutionally effective model in administrative justice.